Simulating Fraunhofer diffraction of waves using microsoft excel spreadsheet. (9th July 2018) - Singh, I; Khun Khun, K; Kaur, B
Abstract: Excel spreadsheets are used as an excellent tool in physics laboratory experiments related to wave optics. This paper presents a simple way to simulate diffraction of waves through a slit using Excel spreadsheets without any tedious programming. These simulations are used to visualize the effect of variation of different parameters such as number of slits, wavelength of incoming light, slit width and slit separation on Fraunhofer diffraction pattern.